A multicentre, randomized, double‐masked, parallel group, vehicle‐controlled phase IIb study to evaluate the safety and efficacy of 1% and 3% topical minocycline gel in patients with papulopustular rosacea. (14th April 2020) - Webster, G.; Draelos, Z.D.; Graber, E.; Lee, M.S.; Dhawan, S.; Salman, M.; Magrath, G.N.
Summary: Background: Papulopustular rosacea is characterized by chronic facial erythema and inflammatory facial lesions. Minocycline has anti‐inflammatory properties which may be effective in the treatment of rosacea inflammatory lesions. Objectives: To assess the safety and efficacy of once‐daily topical minocycline gel 1% and 3% in patients with papulopustular rosacea. Methods: This was a prospective, 12‐week, double‐blinded study conducted at 26 sites in the United States; 270 patients with papulopustular rosacea and 12–40 inflammatory lesions were randomized to minocycline 1%, minocycline 3% or vehicle. The primary endpoint was the mean change in inflammatory lesions at week 12. Key secondary endpoints included success on an Investigator's Global Assessment (IGA). Results: Baseline mean lesion counts were 24·6, 25·1 and 24·3 in the minocycline 1%, minocycline 3% and vehicle groups, respectively; at week 12, the counts had decreased by 12·6, 13·1 and 7·9, respectively. Minocycline significantly decreased lesions, compared with the vehicle [ P = 0·01, 95% confidence interval (CI) 7·9 to 0·9, for minocycline 1%; P = 0·007, 95% CI 8·3 to 1·3, for minocycline 3%]. The proportion of patients achieving IGA success was 39% in the minocycline 1% arm [ P = 0·34, odds ratio (OR) 1·396 and OR 95% CI 0·71 to 2·75 vs. vehicle], 46% in the minocycline 3% arm ( P = 0·04, OR 2·03 and OR 95% CI 1·04 to 3·95 vs. vehicle) and 31% in the vehicle arm. Conclusions: Minocycline topical gel appears to be safe and tolerable at concentrations of 1% and 3%, and both concentrations significantly decreased inflammatory lesion counts, with a significantly larger proportion of patients achieving IGA success at week 12 in the minocycline 3% arm. These findings support further evaluation of minocycline gel for treating inflammatory lesions associated with papulopustular rosacea. Linked Comment: Hampton. Br J Dermatol 2020; 183 :412–413 . Abstract : What is already known about this topic? Papulopustular rosacea is characterized by inflammatory facial lesions and chronic erythema of the face. Oral minocycline has been reported to have efficacy in the treatment of inflammatory lesions of papulopustular rosacea. What does this study add? The study shows that a topical gel preparation of minocycline significantly decreased the number of inflammatory lesions and significantly improved the Investigator's Global Assessment score in patients with papulopustular rosacea. This may offer a topical therapeutic alternative to oral doxycycline or oral minocycline for the treatment of inflammatory lesions in papulopustular rosacea, with potentially fewer systemic side‐effects, owing to lower systemic drug exposure. Linked Comment: Hampton. Br J Dermatol 2020; 183 :412–413 . Plain language summary available online